Understanding Selective Mutism in Very Young Children - Kimberly Renk; Kaitlyn Daleandro; Madison Verdone; Haifa Al-Bassam; Quiyara Murphy (Behavioral Sciences)
Although professionals who work with children and adolescents are well aware of psychological symptom presentations once children and adolescents are in school, such symptom presentations in very young children are less understood. Diagnoses like selective mutism may promote further complications for professionals, as the symptom presentation of anxiety and failure to speak in this diagnosis may overlap with the acquisition of speech and language milestones and problems in very young children. Thus, providing professionals who work with very young children a way to adapt their thinking about selective mutism symptom presentations and interventions is of utmost importance. As a result, this clinically oriented paper will compare DSM-5-TR criteria to DC:0-5 criteria, consider the occurrence of selective mutism symptoms in the context of young children’s speech and language milestones and problems, and reflect upon how intervention adaptations meant to incorporate parents into treatment and account for the capacities of very young children can be helpful in facilitating successful outcomes. It is hoped that having this constellation of clinical information in one place will help providers gain clarity regarding selective mutism symptom presentation and relevant intervention considerations for very young children.